First report of Sharqencyrtus Hayat and Kazmi (Hymenoptera, Encyrtidae) from China, with the description of a new species - Wang, Haiyang; Zhang, Chenghui; Chi, Zhihao; Xue, Hao; Zu, Guohao (Zootaxa, 2023)
The genus Sharqencyrtus Hayat and Kazmi is recorded for the first time from China (Zhejiang province, Yuyao city), and Sharqencyrtus yaobangi Zu, sp. nov., is described as new to science.